Leaf structure and histochemistry of Ficus carica (Moraceae), the fig tree - Mamoucha, S.; Fokialakis, N.; Christodoulakis, N.S. (Flora: Morphology, Distribution, Functional Ecology of Plants, 2016)
Heavily "armed" with trichomes, the hypostomatic leaf of Ficus carica L. is investigated with light and scanning electron microscopy. Histochemical tests were also applied to trace the secondary matabolites produced in the leaf of this well known, Mediterranean tree with the delicious fruits. Numerous idioblasts with crystals, laticifers and sized lythocysts appear within the compact mesophyll. Protective trichomes are located on both surfaces while capitate secretive hairs and stomata appear only abaxially. Stomata, concerning their magnitude, can be assembled in three size-groups in which the arrangement of their parastomatal cells differs as well. Histochemical reactions proved positive only for alkaloids within the laticifers and phenolic compounds, especially for the condensed tannins accumulated within the vacuole of the epidermal cells of this simply constructed leaf with unique features among the Mediterranean herbs. Comparison of GC-MS and LC-HRMS spectra of different extracts of the nerves and, separately, the rest of the leaf, revealed that coumarines such as umbeliferone, psoralen, bergapten and xanthotoxol are probably biosynthetically produced within the nerve area where the highly differentiated, main secretive apparatus of the leaf (laticifers) resides. That is why, these metabolites, are absent from the extracts of the undifferentiated cells derived from in vitro cultures. © 2015 Elsevier GmbH.
Keywords: Ficus (angiosperm); Ficus carica; Laticifers; Leaf anatomy; Moraceae; Secondary metabolites; Secreting activity; Secretory tissues